(untitled) (The Review of Diabetic Studies, 2024)
Background: Epiglottitis and supraglottitis are acute inflammatory conditions of the upper airway that can rapidly progress to life‑threatening airway obstruction. Although once predominantly a pediatric disease caused by Haemophilus influenzae type b (Hib), widespread vaccination has shifted the epidemiology toward adult populations, with distinct clinical presentations and management challenges. Aim: This review aims to provide an updated, comprehensive overview of epiglottitis for healthcare professionals, emphasizing epidemiology, etiology, pathophysiology, clinical presentation, evaluation, and contemporary management strategies across pediatric and adult populations. Methods: A narrative review of the clinical and scientific literature was conducted, integrating historical perspectives with current evidence on microbial causes, risk factors, diagnostic approaches, and airway management principles. Differences between pediatric and adult disease trajectories were highlighted, with particular attention to emergency decision‑making and multidisciplinary care. Results: The incidence of pediatric epiglottitis has markedly declined following Hib vaccination, whereas adult cases now predominate. Bacterial infection remains the most common etiology, although noninfectious and atypical causes are increasingly recognized. Clinical presentation varies by age, with children often displaying abrupt respiratory distress and adults presenting more insidiously. Airway protection is the cornerstone of management, supplemented by broad‑spectrum intravenous antibiotics and, in select cases, corticosteroids. Conclusion: Despite advances in vaccination and airway management, epiglottitis remains a medical emergency with significant morbidity and mortality risk. Early recognition, appropriate airway protection, and coordinated interprofessional management are essential to optimize outcomes.